The design book (New York : Phaidon Press, 2013)
This work features 500 products that have shaped the history of our society and improved the functions of homes,offices, and public buildings all across the world, including information on the designers themselves
Includes index
Keywords: Design -- History -- 19th century; Design -- History -- 20th century; Industrial design -- History -- 19th century; Industrial design -- History -- 20th century